Analysis of Factors Affecting English Language Proficiency of Non-English Education Students - Rusman Rusman; Ita Sarmita Samad; Hasan Hasan (Edumaspul: Jurnal Pendidikan, 2024)
The research aimed to analyze the factors that affected the English language proficiency of students in non-English Education programs at Universitas Muhammadiyah Enrekang. This research was a descriptive research with a qualitative approach. The participants in the research were students from programs outside the English Education program. The data collection method used was a questionnaire. The stages in data analysis included data collection, data reduction, data presentation, and drawing conclusions. The results of the research revealed that the factors affecting the students' English language proficiency were: Listening ability, which was influenced by a lack of vocabulary and concentration, Reading ability, which was influenced by low reading motivation and vocabulary, Speaking ability, which was influenced by a lack of confidence and vocabulary, and Writing ability, which was influenced by low interest and a lack of support from the surrounding environment. This research indicated that the students still faced various challenges in their English language skills, including listening, reading, speaking, and writing, and that additional support outside the classroom was needed to improve their language abilities